Analysis of The Effect of Sales Promotion on Consumer Purchase Decisions at Alfamart in Bengkalis Subdistrict - Nafta Melda Wati Napitupulu; Muhammad Arif; Andri Nofiar. Am (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aimed to analyze respondents' perceptions of sales promotion, respondents' perceptions of consumer purchase decisions, and the effect of sales promotion on consumer purchase decisions at Alfamart in Bengkalis Subdistrict. This study employed an associative research design using a quantitative approach. Data were collected through a questionnaire distributed via a QR code linked to Google Forms, using a non-probability sampling method, specifically the snowball sampling technique. The sample consisted of 100 residents of Bengkalis Subdistrict who had made purchases through sales promotions at Alfamart. The descriptive analysis showed that the sales promotion variable had a mean score of 3.39 (moderate category), while the consumer purchase decision variable had a mean score of 3.44 (high category). Hypothesis testing showed that the calculated t-value (14.265) was higher than the critical t-value (1.661), with a significance value of 0.000 (< α = 0.05). The correlation coefficient (R) was 0.822, and the coefficient of determination (R-squared) was 0.675, indicating that sales promotion influenced consumer purchase decisions by 67.5%, while the remaining 32.5% was explained by other variables not examined in this study. Thus, it can be concluded that sales promotion has a positive and significant effect on consumer purchase decisions at Alfamart in Bengkalis Subdistrict. Therefore, Ho was rejected, and Ha was accepted.